2012
DOI: 10.1111/jch.12029
|View full text |Cite
|
Sign up to set email alerts
|

Low Nadir CD4 Cell Count Predicts Sustained Hypertension in HIV‐Infected Individuals

Abstract: Hypertension is associated with cardiovascular disease in the human immunodeficiency virus (HIV)-infected population. The authors aimed to test the hypothesis whether advanced immunosuppression with low nadir CD4 lymphocyte cell count is a predictor of sustained hypertension in HIV-infected individuals. In a longitudinal study of an HIV cohort of 434 patients (43AE11 years, 72% men, 71% Caucasians), standardized blood pressure was measured in duplicate during 3 clinical visits both at baseline and after 3.4AE0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
43
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 44 publications
8
43
4
Order By: Relevance
“…The hypothesized immunologic mechanisms of cardiovascular disease in HIV-infected adults are multiple, including activation of endothelial cells, immune activation, and alteration in lipid function [40]. While some studies have shown either CD4 or CD8 lymphocyte measures are independent predictors of cardiovascular disease outcomes, others have found no association [13, 4145]. Of note, CD4/CD8 ratio has been observed to show less intra-individual variability over time compared to either CD4 or CD8 lymphocyte counts [20].…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesized immunologic mechanisms of cardiovascular disease in HIV-infected adults are multiple, including activation of endothelial cells, immune activation, and alteration in lipid function [40]. While some studies have shown either CD4 or CD8 lymphocyte measures are independent predictors of cardiovascular disease outcomes, others have found no association [13, 4145]. Of note, CD4/CD8 ratio has been observed to show less intra-individual variability over time compared to either CD4 or CD8 lymphocyte counts [20].…”
Section: Discussionmentioning
confidence: 99%
“…88 Based on our recent finding of an association between low nadir CD4 count and the development of sustained hypertension, 89 we hypothesized that measures of microbial translocation would predict hypertension in ART-naive patients. Indeed, plasma levels of both LPS and sCD14 at the time of nadir were elevated in HIVinfected compared to controls, predicted sustained hypertension, and were intercorrelated in subjects who developed hypertension several years later.…”
Section: Hypertensionmentioning
confidence: 99%
“…Findings from several epidemiologic studies support a highly plausible relationship between profound immune depression and the development of hypertension among HIVinfected individuals. Manner et al [31] observed that low nadir CD4 þ T-cell count was an independent and strong predictor of sustained hypertension in a longitudinal study of 434 HIV-infected individuals with a mean follow-up of 3.4 AE 0.8 years. Other studies also observed that the development of hypertension [32,33] or its higher prevalence [34] was independently associated with nadir CD4 þ T-cell count less than 200 cells/ml or lower baseline CD4 þ T-cell count along with traditional risk factors in HIV-infected individuals.…”
Section: Vascular Aging In Hiv-infected Individualsmentioning
confidence: 97%